Evaluating methods for determining mercury concentrations in ancient marine fish and mammal bones as an approach to assessing millennial-scale fluctuations in marine ecosystems - Avery, Julie P.; Castellini, J. Margaret; Misarti, Nicole; Keenan, Mary; Gastaldi, Angela; Funk, Caroline; O’Hara, Todd M.; Rea, Lorrie D. (Frontiers in Ecology and Evolution, 2023)
Millennial-scale datasets of heavy metals in biota are difficult to obtain but are important for determining patterns and underlying drivers of toxicant concentrations. This is particularly important to better discriminate contemporary natural and anthropogenic sources. Globally mercury is a contaminant of concern. Post-industrial increases in mercury in arctic biota have been documented and monitoring of Steller sea lions (Eumetopias jubatus) in the Aleutian Islands, Alaska, has revealed a high proportion of pups with fur mercury concentrations above thresholds of concern in some regions. As bone is a tissue that is well preserved in archeological middens, it may prove useful for developing long-term mercury data sets under appropriate conditions. The goal of this study was to evaluate methodologies for measuring mercury concentration in Steller sea lion bone using a direct mercury analyzer, considering sample preparation methods and variability among bone tissue types (e.g., compact versus spongy bone). Finally, we directly compare sensitivity and precision of two different direct mercury analyzer models. Based on the methods presented here, direct mercury analysis using the Nippon MA-3000 can quantify small (ppb) quantities of Hg accurately and precisely in 20 to 60mg of bone with minimal specimen processing. The described method is efficient, relatively inexpensive, and requires minimal bone, conserving rare and valuable specimens. Hydrogen peroxide cleaning and collagen extraction were not required, and may be detrimental for optimal Hg quantification in bone. Further, while homogenization of distinct compact and spongy bone did not impact concentration determination, variance of technical replicates was lower improving quantitation precision. Most importantly, significant differences between compact and spongy bone exist within some individual specimen; however, the difference is not consistent and may indicate differential Hg exposure windows influenced by turnover rate of bone types. We conclude bone provides a natural archive for mercury ecosystem dynamics over millennial time scales in regions where appropriate samples are available. Compact bone has lower and less variable [THg] simplifying analysis and interpretation of data; however, the more dynamic concentrations observed in spongy bone should not be dismissed as invaluable due to their variability in [THg]. Comparisons of [THg] between bone type within individual may provide insight into more acute changes in mercury exposure within an individual’s lifetime.